Дизайн гільзи стегна - Терентьєв, А. В.; Дацок, О. М. (ХНУРЕ, 2019)
This work is devoted to the comparative characteristics of the structures of sockets for hip prostheses. Here both advantages and disadvantages of each of the presented forms of sockets used in modern prosthetics are shown. Long-term studies show that the longitudinal-oval shape of the socket is really anatomically correct, comfortable, and also biomechanically functional for the patient when using a hip prosthesis.
Keywords: стегно; протезування